2009
DOI: 10.4049/jimmunol.0804295
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Primary and Secondary Effects of CD19 Deficiency on Cells of the Marginal Zone

Abstract: Marginal zone (MZ) B cells are absent in CD19−/− mice. Possible causes include an intrinsic defect in B cells and/or a secondary defect in the extrinsic MZ microenvironment as a result of changes in B cell differentiation in mice lacking CD19. Cells in the MZ also include MZ macrophages (MZM) and MZ dendritic cells (DC). Although CD19 is only expressed on B cells, SIGN-R1+ MZM are absent and CD11c+ MZ DC distribution is abnormal in CD19−/− mice. Adoptively transferred B cells from normal mice are able to recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 20 publications
8
40
0
Order By: Relevance
“…Hence, we suggest that MZBs are involved in shuttling of dexosomes from the blood to FDCs, leading to activation of B cells and CD4 + T cells. The transport of dexosomes by MZBs might be mediated by complement, because MZBs are involved in complement receptor CD21-dependent transport of immune complexes (23), and several complement factors were shown to be present on dexosomes (24). In accordance, dexosome transport by MZBs is plausible because we find that noncognate MZBs readily bind dexosomes (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Hence, we suggest that MZBs are involved in shuttling of dexosomes from the blood to FDCs, leading to activation of B cells and CD4 + T cells. The transport of dexosomes by MZBs might be mediated by complement, because MZBs are involved in complement receptor CD21-dependent transport of immune complexes (23), and several complement factors were shown to be present on dexosomes (24). In accordance, dexosome transport by MZBs is plausible because we find that noncognate MZBs readily bind dexosomes (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…It has been reported that CD74 2/2 B cells have a defective Ag presentation, which leads to preferential Th1 response (41), and that CD19 2/2 mice mount impaired responses to T-dependent Ags and lack B1 (25,32) and MZ B cells (42). Although this critique is important to consider, we believe it does not reduce the scope and/or the extent of our findings, for several reasons.…”
Section: Discussionmentioning
confidence: 62%
“…Although there are some caveats to this trend (50,51), these data have led to the hypothesis that weaker BCR signaling favors differentiation of MZ B cells and stronger signaling favors FO B cell differentiation (38). Despite significantly increased differentiation of MZ B cells in NOD mice, our experiments examining protein phosphorylation and calcium flux induced by BCR stimulation (Fig.…”
Section: Discussionmentioning
confidence: 94%